Walking exercise intervention for 4 weeks mitigates cold symptoms in young women with a cold constitution - Fumio Yamazaki; Yume Araki; Sayaka Takuno; Ayuka Hamada (Journal of Physical Fitness and Sports Medicine, 2021)
The purpose of this study was to clarify the effect of aerobic exercise training on the coldness of the body and physiologically-related factors in Japanese young women with cold constitution. Eighteen subjects were divided into two groups: exercise (E) and non-exercise control (C) groups. Subjects in the E group performed exercise training of fast walking 4 days or more per week for 4 weeks. The training significantly decreased the scores for cold feeling in the fingertips and toes, but did not change the metabolic rate or sublingual and skin temperatures in the hands and feet during rest under normothermic conditions. In the C group, all variables remained unchanged throughout the 4-week control period. These results suggest that aerobic exercise mitigated coldness in the distal portion of the extremities via the reduction of cold sensation at a normal body temperature in young women complaining of chilliness.